Evaluation of Fluorescence Intensity and Antitumor Effect Using Real-Time Imaging in Photoimmunotherapy - Kenji Takashima; Yoshikatsu Koga; Takahiro Anzai; Kayo Migita; Toru Yamaguchi; Akihiro Ishikawa; Shingo Sakashita; Masahiro Yasunaga; Tomonori Yano (MDPI AG, 2022)
Photoimmunotherapy (PIT) is a promising tumor-selective treatment method that uses light-absorbing dye-conjugated antibodies and light irradiation. It has been reported that IR700 fluorescence changes with light irradiation. The purpose of this study was to investigate the fluorescence intensity and antitumor effect of PIT using real-time fluorescence observation of tumors and predict the required irradiation dose. The near-infrared camera system LIGHTVISION was used to image IR700 during PIT treatment. IR700 showed a sharp decrease in fluorescence intensity in the early stage of treatment and almost reached a plateau at an irradiation dose of 40 J/cm. Cetuximab-PIT for A431 xenografts was performed at multiple doses from 0-100 J/cm. A significant antitumor effect was observed at 40 J/cm compared to no irradiation, and there was no significant difference between 40 J/cm and 100 J/cm. These results suggest that the rate of decay of the tumor fluorescence intensity correlates with the antitumor effect by real-time fluorescence imaging during PIT. In addition, when the fluorescence intensity of the tumor plateaued in real-time fluorescence imaging, it was assumed that the laser dose was necessary for treatment.